Long‐term trends indicate that invasive plants are pervasive and increasing in eastern national parks. Issue 2 (15th November 2020) - Miller, Kathryn M.; McGill, Brian J.; Weed, Aaron S.; Seirup, Camilla E.; Comiskey, James A.; Matthews, Elizabeth R.; Perles, Stephanie; Paul Schmit, John
Abstract: While invasive plant distributions are relatively well known in the eastern United States, temporal changes in species distributions and interactions among species have received little attention. Managers are therefore left to make management decisions without knowing which species pose the greatest threats based on their ability to spread, persist and outcompete other invasive species. To fill this gap, we used the U.S. National Park Service's Inventory and Monitoring Program data collected from over 1, 400 permanent forest plots spanning 12 yr and covering 39 eastern national parks to analyze invasive plant trends. We analyzed trends in abundance at multiple scales, including plot frequency, quadrat frequency, and average quadrat cover. We examined trends overall, by functional group, and by species. We detected considerably more increasing than decreasing trends in invasive plant abundance. In fact, 80% of the parks in our study had at least one significant increasing trend in invasive abundance over time. Where detected, significant negative trends tended to be herbaceous or graminoid species. However, these declines were often countered by roughly equivalent increases in invasive shrubs over the same time period, and we only detected overall declines in invasive abundance in two parks in our study. Present in over 30% of plots and responsible for the steepest and greatest number of significant increases, Japanese stiltgrass ( Microstegium vimineum ) was the most aggressive invader in our study and is a high management priority. Invasive shrubs, especially Japanese barberry ( Berberis thunbergii ), Japanese honeysuckle ( Lonicera japonica ), multiflora rose ( Rosa multiflora ), and wineberry ( Rubus phoenicolasius ), also increased across multiple parks, and sometimes at the expense of Japanese stiltgrass. Given the added risks to human health from tick‐borne diseases, invasive shrubs are a high management priority. While these findings provide critical information to managers for species prioritization, they also demonstrate the incredible management challenge that invasive plants pose in protected areas, particularly since we documented few overall declines in invasive abundance. As parks work to overcome deferred maintenance of infrastructure, our findings suggest that deferred management of natural resources, particularly invasive species, requires similar attention and long‐term commitment to reverse these widespread increasing invasive trends.